2021
DOI: 10.1145/3406533
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Fuzzy Game-Based Energy-Efficient Localization in 3D Underwater Sensor Networks

Abstract: Numerous applications in 3D underwater sensor networks (UWSNs), such as pollution detection, disaster prevention, animal monitoring, navigation assistance, and submarines tracking, heavily rely on accurate localization techniques. However, due to the limited batteries of sensor nodes and the difficulty for energy harvesting in UWSNs, it is challenging to localize sensor nodes successfully within a short sensor node lifetime in an unspecified underwater environment. Therefore, we propose the Adaptive Energy-Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The process of localization is performed in two parts: (1) Offline phase for training EELA, train data for several routing protocols, (2) online phase, the anchor node sends the awakening signal with the least amount of transmission energy to begin the localization process. 51 iii. Iterative localization mechanism based on error control (ILMEC): Prior to localization, ILMEC develops a multi-path generation approach to establish the localization order and transmission power of each known node.…”
Section: Received Signal Strength Indicator (Rssi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The process of localization is performed in two parts: (1) Offline phase for training EELA, train data for several routing protocols, (2) online phase, the anchor node sends the awakening signal with the least amount of transmission energy to begin the localization process. 51 iii. Iterative localization mechanism based on error control (ILMEC): Prior to localization, ILMEC develops a multi-path generation approach to establish the localization order and transmission power of each known node.…”
Section: Received Signal Strength Indicator (Rssi)mentioning
confidence: 99%
“…Inside this approach, the regular node serves as the leader, while the reference node serves as the follower, capable of locating nodes by using the least amount of power. Adaptive EELA: It employs a fuzzy player approach, whereas the Stackelberg game is used to design the interactions between sensor and anchor nodes in UWSNs, as well as this technique is used to fix the appropriate usage activities. The process of localization is performed in two parts: (1) Offline phase for training EELA, train data for several routing protocols, (2) online phase, the anchor node sends the awakening signal with the least amount of transmission energy to begin the localization process 51 Iterative localization mechanism based on error control (ILMEC): Prior to localization, ILMEC develops a multi‐path generation approach to establish the localization order and transmission power of each known node.…”
Section: Classification Of Node Localization In Uwsnmentioning
confidence: 99%
“…RSS-based energy-efficient localization algorithm (EELA) 25,26 Transmission power Provide optimal solution for efficient power usage.…”
Section: Coverage and Localization Ratiomentioning
confidence: 99%
“…Yuan et al 26 have suggested the “Adaptive Energy‐Efficient Localization Algorithm” named as adaptive EELA. This algorithm consumes less energy of nodes whilst responding to dynamic topology variations.…”
Section: Literature Surveymentioning
confidence: 99%